Extraordinary Investigation Power of the Anti-Corruption Agencies in Indonesia and Singapore - Andreas Calvin (Tumou Tou Law Review, 2024)
Corruption is one of the serious crimes people worldwide need to deal with. It is even considered the largest problem in the world. The large negative impact of corruption urges the Criminal Justice System from countries around the world to adjust, to tackle it more effectively and faster. Some countries choose to do that by introducing an Anti-Corruption Agency (ACA). This research aims to improve Indonesia's Criminal Justice System in tackling Corruption, especially regarding the Investigation Power given to the KPK, by using a Comparative Approach between the Anti-Corruption Agencies in Indonesia (KPK) and Singapore (CPIB). The functional method of the comparative approach was used in this article, starting from the problem of corruption and then seeing how both countries deal with it through their own Anti-Corruption Agencies, especially in the power and authority given to the agencies. This research finds that there are some exceptional Investigation Powers given to both the CPIB and KPK in order to combat corruption. Although there are some exceptional powers given to the CPIB, the power given to KPK steps even further. However, in the last 20 years, Singapore has been constantly ranked as one of the best countries in terms of combating corruption according to the Corruption Perception Index. On the other hand, since the establishment of KPK in 2002, we see that until now, the Corruption Perception Index in Indonesia does not show significant changes. It does raise the question of whether this exceptional Investigation Power given to the ACA is needed to combat corruption. Although it is still necessary, the author suggests it should not be the main focus in combating corruption. A more thorough and comprehensive approach to combat corruption should be considered rather than just increasing the power of the ACA.